Human security and the rise of global therapeutic governance - Pupavac, Vanessa (Routledge, 2005)
This article discusses the emergence of global therapeutic governance or the influence of social psychology on international development policy. Therapeutic governance links psychosocial well-being and security, and seeks to foster personalities able to cope with risk and insecurity. The article analyses how Western alarm at the destabilising impact of development eroded its support for an industrialisation model of development. The article then examines how the basic needs model is underpinned by social psychological theories and involves an abandonment of national development. Finally the article considers development as therapeutic governance and the implications of abandoning national development for the concept of human security. A final version of this article appeared as follows Vanessa Pupavac ‘Human Security and the Rise of Global Therapeutic Governance.’ Conflict, Security and Development, Vol 5 (2), 2005, pp. 161-181.